Digital communication strategy of Ayam Ambara restaurant in increasing customer engagement - Daffa Aulia Hasan; Ruhimat Ruhimat; Robby Firliandoko (Privietlab, 2026)
The transformation of marketing communication practices in the culinary sector has shifted significantly from conventional approaches to more interactive digital channels. This study aimed to analyze the digital communication strategy implemented by Ayam Ambara Restaurant in building its online presence. A descriptive qualitative approach was employed in this research. Data were gathered through online observations on official digital platforms, in-depth semi-structured interviews with the restaurant owner, social media administrators, and active customers, as well as documentation analysis of social media content. The informants were selected using a purposive sampling technique. Data validation was achieved through source and technique triangulations, while data analysis followed the qualitative interactive model including data condensation, data display, and conclusion drawing. The results demonstrated that Ayam Ambara effectively operationalized the principles of digital interactivity and hypertextuality across TikTok and Instagram. The creation of a casual, highly responsive, and humanized administrator persona minimized the psychological distance between the brand and its audience, actively turning passive viewers into engaged followers. Furthermore, structured cross-platform hypertextual integration successfully streamlined the consumer journey, transforming cognitive interest into behavioral and transactional actions. In conclusion, a well-planned digital communication strategy that balances aesthetic content marketing with organic interactive management plays a pivotal role in boosting customer engagement within the local culinary industry.